Brain and serum metabolomic studies reveal therapeutic effects of san hua decoction in rats with ischemic stroke - Liu, Ruisi; Cao, Shengxuan; Cai, Yufeng; Zhou, Mingmei; Gou, Xiaojun; Huang, Ying (Frontiers in Endocrinology, 2023)
San Hua Decoction (SHD) is a traditional four-herbal formula that has long been used to treat stroke. Our study used a traditional pharmacodynamic approach combined with systematic and untargeted metabolomics analyses to further investigate the therapeutic effects and potential mechanisms of SHD on ischemic stroke (IS). Male Sprague-Dawley rats were randomly divided into control, sham-operated, middle cerebral artery occlusion reperfusion (MCAO/R) model and SHD groups. The SHD group was provided with SHD (7.2 g/kg, i.g.) and the other three groups were provided with equal amounts of purified water once a day in the morning for 10 consecutive days. Our results showed that cerebral infarct volumes were reduced in the SHD group compared with the model group. Besides, SHD enhanced the activity of SOD and decreased MDA level in MCAO/R rats. Meanwhile, SHD could ameliorate pathological abnormalities by reducing neuronal damage, improving the structure of damaged neurons and reducing inflammatory cell infiltration. Metabolomic analysis of brain and serum samples with GC-MS techniques revealed 55 differential metabolites between the sham and model groups.Among them, the levels of 12 metabolites were restored after treatment with SHD. Metabolic pathway analysis showed that SHD improved the levels of 12 metabolites related to amino acid metabolism and carbohydrate metabolism, 9 of which were significantly associated with disease.. SHD attenuated brain inflammation after ischemia-reperfusion. The mechanisms underlying the therapeutic effects of SHD in MCAO/R rats are related to amino acid and carbohydrate metabolism.